Loss of SNORA73 reprograms cellular metabolism and protects against steatohepatitis - Arthur C. Sletten (Nature Portfolio, 2021)
Lipid induced stress contributes to metabolic diseases. Here the authors identify small nucleolar RNA 73 (SNORA73) in a screen for genes that protect against lipotoxicity and show that deficiency of SNORA73 reprograms oxidative metabolism and protects against steatohepatitis in mice.